Stembark Methanol Extract of P. americana: Total Antioxidant Capacity, Total Flavonoids Content, Total Phenolics Content and Its Flavonoids, Vitamins and Amino Acids Profile - Yakubu, Ojochenemi E.; Abu, Michael S.; Danjuma, Janya; Umaru, Isaac John; Oladele, Gloria Omonefe (Darul Yasin Al Sys, 2024)
This research investigated the total antioxidant capacity, total flavonoids content, total phenolics content as well the flavonoids, vitamins and amino acids profile of stembark methanol extract of P. americana. Plant materials have been known be rich source of various medicinal active ingredients. These may include alkaloids, terpenoids, saponins, phenolic compounds, flavonoids, and tannins as well as nutritional components including sugars, amino acids as well as proteins in addition to other vital components. The stembark of P. americana was harvested in its plant in Baissa, Taraba State, Nigeria. The plant material was air dried and pulverized and soaked in methanol for 72 hours before filtration. The filtrate was further concentrated using rotary evaporator and water bath. The concentrate was analyzed for total antioxidant capacity using DPPH, flavonoids content using aluminium chloride and phenolics content using folin ciocaltue. Flavonoids, vitamins and amin acids profile was determined using HPLC. The result total antioxidant capacity shows that inhibition increased with concentration with the 100µL/100mL had inhibition percentage of 87.88% whereas the lowest concentration of 31.25µL/100mLhad the inhibition percentage of 40.14%. The results for total flavonoid content and total phenolics content show significant levels with 42.21±0.23mg QE/100g and 33.65±3.02mg GAE/100g respectively. The result for flavonoid and phenolics profile reveals that quercetin and caffeic acid phenyl ester were identified with 0.50% and 99.50% respectively. For vitamins, vitamin K was detected with 0.40%, vitamin B1 with 80.20% and vitamin B2 with 19.50% abundance. There seven different amino acids identified, these include asparagine, threonine, phenylalanine, aspartic acid, glutamic acid, leucine and arginine. The outcomes reveal that the plant material could possess important phytochemicals which could be used in disease treatment as well as vital macromolecules that can be used as supplements.